Ideologies of Poets in The Last 10 Years - Maria, Dilla; Helmanto, Fachri; Hasnin, Hanrezi Dhania (Mitra Palupi, 2024)
Background: The poet's ideas have broad meaning and a landscape of human emotions that reaches the hidden corners of the universe. Bibliometrics is an analytical method used to quantitatively measure literature and scientific publications. Purpose: In the context of ideas, bibliometrics can provide valuable insight into how many ideas have been explored, how often ideas are cited, and how they develop and are shared within the scientific community. Design and methods: This research uses a research method using a literature review with the help of Publish or Perish and VOSviewer to obtain data. Results: Search results using Publish or Perish are then presented via VOSviewer, containing several elements of ideas or ideologies that have been researched in 200 journals from 2014-2024. These journals also contain 988 quotes from poets of that time. This shows that the poet's ideas are still relevant and widely discussed in scientific literature in the last ten years.